(untitled) (Ameghiniana, 2013)
ABSTRACT: Bifungites sp. (TRACE FOSSIL) FROM THE LOWER ORDOVICIAN BEDS OF THE PERCHELREGlON,QUEBRADA DE HUMAHUACA,JUJUY PROVINCE.- The fírst appearance of Bifungites sp. (trace fossil) in Ordovician rocks from South America is reported. This trace fossil, an important paleoenvironmental indica tor, is present in association with trilobite traces (Monomorphichnus) and others, in the outcrops of the basal levels of the Tremadoeían beds in Perchel afea, province of Jujuy, Argentina.